2016
DOI: 10.7717/peerj.1591
|View full text |Cite
|
Sign up to set email alerts
|

The Iflaviruses Sacbrood virus and Deformed wing virus evoke different transcriptional responses in the honeybee which may facilitate their horizontal or vertical transmission

Abstract: Sacbrood virus (SBV) and Deformed wing virus (DWV) are evolutionarily related positive-strand RNA viruses, members of the Iflavirus group. They both infect the honeybee Apis mellifera but have strikingly different levels of virulence when transmitted orally. Honeybee larvae orally infected with SBV usually accumulate high levels of the virus, which halts larval development and causes insect death. In contrast, oral DWV infection at the larval stage usually causes asymptomatic infection with low levels of the v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
81
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(95 citation statements)
references
References 45 publications
11
81
2
1
Order By: Relevance
“…Thus, it is either possible that the higher expression of the immune genes observed in foragers can be a response to increased DWV infection, or that this immune expression occurs before the increase in viral infection. Still, the close association observed between ppo expression and DWV titers, which has been documented in winter bees (Steinman 2015) is remarkable and consistent with the association between the cellular immune response and viral infections reported previously in honey bees and other insects [110113].…”
Section: Discussionsupporting
confidence: 88%
“…Thus, it is either possible that the higher expression of the immune genes observed in foragers can be a response to increased DWV infection, or that this immune expression occurs before the increase in viral infection. Still, the close association observed between ppo expression and DWV titers, which has been documented in winter bees (Steinman 2015) is remarkable and consistent with the association between the cellular immune response and viral infections reported previously in honey bees and other insects [110113].…”
Section: Discussionsupporting
confidence: 88%
“…The DEGs identified in SINV-GFP-infected bees 72 hpi were compared to those identified in naturally IAPV-infected bees (Chen et al . 2014, orange) 9 , bees infected with IAPV via oral inoculation (Galbraith et al ., 2015, green) 24 , SBV and DWV-infected bees (Ryabov et al ., 2016, pink) 25 , and a common DEG list that was compiled from 19 gene expression data sets including Varroa destructor -parasitized and virus-infected bees (Doublet et al ., 2017) 92 (purple). Lists of DEGs from all studies that were used to generate the Venn diagram 131 are provided in Supplementary Tables S14 and Venn diagram results are listed in S15. …”
Section: Resultsmentioning
confidence: 99%
“…The Kenyan clade of honey bee adults and brood share related BQCV strains with their Varroa mites. The mite Varroa destructor vectors several viruses (McMenamin and Genersch, ; Ryabov et al ., ). Additionally, we found that BQCV isolated from the fungus Ascosphaera apis from honey bees in Maryland clustered with our New York honey bee and native bee samples, illustrating the close relatedness of the virus and potential for virus crossover between fungal and bee species.…”
Section: Discussionmentioning
confidence: 97%
“…While the virus can be detected in honey bee workers, it is not typically a lethal infection in this caste. DWV is often asymptomatic and found at low levels in a honey bee colony, however, direct injection by the Varroa mite causes high pathogenicity (Ryabov et al, 2016). This is the most common virus found in non-Apis hosts, present in 19 species (Tehel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%